2009
DOI: 10.1093/ndt/gfp484
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of peritoneal ultrafiltration in the treatment of refractory congestive heart failure

Abstract: We demonstrate that congestive HF programmes should consider offering PD in hope of seeing better functional status, reduced morbidity and mortality, better quality of life as well as reduced health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 14 publications
18
127
3
8
Order By: Relevance
“…To mitigate IDWG-related harm, non-HD day therapies, such as adjunct PD and wearable UF devices, may be beneficial. PD in patients with refractory heart failure has been shown to decrease hospitalizations and improve functional status (17). In a 13-patient study of 4-weeks duration, Jones et al (18) showed lower pre-HD BP and IDWG among patients treated with near daily UF (4 days of UF and 2 days of UF and HD).…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate IDWG-related harm, non-HD day therapies, such as adjunct PD and wearable UF devices, may be beneficial. PD in patients with refractory heart failure has been shown to decrease hospitalizations and improve functional status (17). In a 13-patient study of 4-weeks duration, Jones et al (18) showed lower pre-HD BP and IDWG among patients treated with near daily UF (4 days of UF and 2 days of UF and HD).…”
Section: Discussionmentioning
confidence: 99%
“…That reduction can be considered an indirect marker of improved quality of life in the patients and also a surrogate marker of better control of HF symptoms and signs. As a disease, HF is costly: 2% of the total health care budget in European countries is used for expenses related to its management (25). Rates of re-hospitalization for acute decompensated HF are as high as 20% in 6 months, and costs linked to hospitalizations represent two thirds of the total cost of the disease (2).…”
Section: Pd In Heart Failure Patients Refractory To Diureticsmentioning
confidence: 99%
“…In many of the other studies that examined the effect of PUF on GFR, PUF was found to be ineffective on GFR (42,56,68,79). In a meta-analysis including six studies with a total of 282 patients without indications of renal replacement therapy, there was no significant difference in GFR before and after PUF (80).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 99%
“…One reason for the increase in EF is thought to be the removal of cardio depressant agents by PD (66). In many of these studies, the exercise capacities of HF patients were assessed by the NYHA classification and the results shows that NHYA class regresses and EF increases with PUF (58,(67)(68)(69)(70)(71)(72)(73).…”
Section: How Does Peritoneal Dialysis Affect Ejection Fraction or Newmentioning
confidence: 99%
See 1 more Smart Citation